IMPLEMENTATION OF THE GRANTING OF LAND OWNERSHIP RIGHTS BY THE STATE FOR FOREIGN CITIZENS UNDER ARTICLE 21 PARAGRAPH 3 OF THE BASIC AGRARIAN LAW - Ratu, Ida Ayu Mas; Santika, Ida Bagus Agung Putra (jfpublisher, 2024)
Land or land rights can be obtained by someone as an heir, either a biological child or a living spouse, either individually or jointly between the biological child and the living spouse. The acquisition of property rights over land occurs through inheritance, which is the transfer of land rights due to the death of a person or heir who holds land rights. The objective of this research is to identify and analyze the regulation of land ownership rights for foreign nationals according to Article 21 Paragraph 3 of the Basic Agrarian Law (UUPA) and to identify and comprehend the implementation of land ownership rights by the State for foreign nationals at the Badung Regency Land Office. This research applies empirical legal research method with statutory approach, legal concept analysis and factual approach. The results of this research indicate that the regulation of the acquisition of property rights to land for foreign nationals according to Article 21 Paragraph 3 of the Basic Agrarian Law is that heirs with foreign citizenship are obliged to relinquish the right within a period of 1 year since the loss of Indonesian citizenship. The implementation of the granting of land ownership rights by the State for foreign nationals in the Badung Regency Land Office is that a foreign national may receive inheritance of land and/or buildings with property rights status (such as a house). However, within one year, the foreign national must transfer his/her rights to the land and/or building to another person.